1993
DOI: 10.1073/pnas.90.5.1887
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin D-deficient mice can mount normal immune responses to thymus-independent and -dependent antigens.

Abstract: To examine the in vivo function of IgD we generated mice deficient for IgD by gene targeting. The IgDmice show a reduced B-cell compartment with 30-50% less B cells in the spleen and lymph nodes but show a normal pre-B-cell compartment. The surface-IgD-B cells express two to three times more surface IgM than B cells ofcontrol animals. Serum concentrations of the immunoglobuln isotpes of IgDmice are almost normal, indicating that surface-IgD expression is not necessary for class switching of B cells. Immunizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
83
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 32 publications
10
83
2
Order By: Relevance
“…Tg mice expressing mb IgD and IgM have an increased mature B cell pool (29) compared with tg mice expressing only mb IgM. Our results, even though originating from single IgM and IgM/IgD tg lines, are consistent with these data and those of others (30). nAAb B cells exit from the bone marrow whether they express IgD or not, but the proportion of peripheral immature B cells (AA 4.1 positive, CD23 negative) is significantly higher in tg mice that express only IgM.…”
Section: Discussionsupporting
confidence: 82%
“…Tg mice expressing mb IgD and IgM have an increased mature B cell pool (29) compared with tg mice expressing only mb IgM. Our results, even though originating from single IgM and IgM/IgD tg lines, are consistent with these data and those of others (30). nAAb B cells exit from the bone marrow whether they express IgD or not, but the proportion of peripheral immature B cells (AA 4.1 positive, CD23 negative) is significantly higher in tg mice that express only IgM.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, IgD is a class of antibody that is considered to have evolved relatively recently, having been described only in primates and rodents (7)(8)(9)(10). Although the function, biochemistry and genetics of IgD have been the subject of intense interest (11)(12)(13)(14)(15)(16)(17) gene targeting (knockout) experiments revealed that IgD had a relatively minor functional role in immune responses in the mouse (18,19). We report here the results of studies that identify a complex homolog of the IgD heavy (H) (␦) chain in the channel catfish (Ictalurus punctatus).…”
mentioning
confidence: 88%
“…IgD-deficient mice respond well to T cell-independent and -dependent antigens, but affinity maturation is delayed in the early primary response compared to control animals [6], suggesting that there may be differences in the function of IgM and IgD as antigen receptors. In addition, it has been shown that IgD -/-mice have 30-50% fewer B cells in the spleen and lymph nodes than IgD +/+ mice [7], suggesting that IgD may have a role in B cell homeostasis. In IgM -/-mice, B cell development and maturation proceed normally, with IgD replacing IgM [8].…”
Section: Introductionmentioning
confidence: 99%